Heads up how to anticipate business surprises and seize opportunities first - McGee, Kenneth G. (Harvard Business School Press, 2004)
"Based on five years of proprietary research by Gartner, Inc., Heads Up reveals that even the worst business disasters rarely happen without warning - and more important, that individual managers can break this pervasive pattern of surprises followed by desperate responses. McGee's research shows that no more than 5 percent of available data is necessary to end business surprises. Instead of trying to predict the future, what managers really need to master is predicting the present: understanding what is happening right now in mission-critical parts of their business. In this book, McGee shows managers how to identify which pieces of data are needed in real time so that effective responses can be deployed at the right time - thereby avoiding disasters and seizing opportnities before it's too late."--Jacket.